Structural characterization of a novel acidic polysaccharide from Rosa roxburghii Tratt fruit and its α-glucosidase inhibitory activity. Issue 7 (5th July 2018) - Wang, Lei; Chen, Chun; Zhang, Bin; Huang, Qiang; Fu, Xiong; Li, Chao
Abstract : An acidic polysaccharide (RTFP-3) extracted from Rosa roxburghii Tratt fruit can inhibit the activity of α-glucosidase. Abstract : A novel acidic polysaccharide (RTFP-3) was isolated and purified from Rosa roxburghii Tratt fruits. Structural analyses revealed that RTFP-3 is a homogeneous polysaccharide with a molecular weight of 67.2 kDa and mainly consists of arabinose (37.20%), galactose (34.40%), glucose (10.02%) and fucose (18.30%). The structural chain of RTFP-3 was proven to be composed of →6)-α-d -Gal p -(1→, →4)-α-d -Gal p A-(1→, →5)-α-l -Ara f -(1→, →4)-β-d -Glc p -(1→, β-d -Glc p -(1→ and →3, 4)-β-l -Fuc p -(1→ residues by periodate oxidation–Smith degradation, methylation, and 1D- and 2D-NMR analyses. Bioassay results showed that RTFP-3 exerted favorable mixed type inhibitory activities against α-glucosidase, and its half inhibitory concentration (IC50 ) value was determined as 4.15 mg mL −1 . RTFP-3 showed static type quenching of the intrinsic fluorescence of α-glucosidase, during which the binding process induced the conformational change of α-glucosidase. These results suggest that RTFP-3 has the potential to be a novel α-glucosidase inhibitory agent for use in functional foods.